A non-gradient-based reliability method using a new six-item instruction for updating design point. (April 2023) - Amin Roudak, Mohammad; Karamloo, Mohammad; Ali Shayanfar, Mohsen; Ardalan, Rojin
Abstract: Reliability analysis of structures without spending too much computational cost is still a challenge. In this paper, an efficient non-gradient-based reliability method is proposed for analyzing the structures in which limit state functions are not explicitly known. Starting from an initial guess of design point, the proposed method updates this estimation of design point to approach the real one. A new comprehensive six-item instruction, represented for updating the estimations of the design point, is the main component of the proposed method in finding the solution. Due to including various conditions in the proposed instruction, the improvement of MPP candidates does not stop easily. To investigate the performance of this reliability method, at first, it is implemented in a number of mathematical problems of the literature. Then, structural problems, including a five-story steel building with implicit limit state functions and uncertain data are analyzed to show the applicability of the proposed method in real structures. The results of the mathematical and structural problems clearly show the efficiency and applicability of the proposed method.